Rising energy prices and advances in renewable energy technologies - Sherief Emam; Thomas Grebel (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
In this paper we investigate the impact of rising energy prices on technological progress in the market for renewable energies. We use patent data of OECD countries from 1970 to 2010 and test the impact of oil prices on the innovative success of countries; R&D, investment activities, electricity consumption, etc. are used as control variables. We compare several models such as Pooled Mean Group (PMG), Mean Group (MG), Count data (CD) and Dynamic fixed effects (DFE) models to distinguish short and long-term effects. The preliminary results show that increasing energy prices seem to encourage innovation in renewable energy technologies.
Keywords: Q55; C23; 330; Renewable Energy; Heterogeneous Dynamic Panel Data; Technological Progress